2022
DOI: 10.1002/advs.202201621
|View full text |Cite
|
Sign up to set email alerts
|

A Neuroimaging Signature of Cognitive Aging from Whole‐Brain Functional Connectivity

Abstract: Cognitive decline is amongst one of the most commonly reported complaints during normal aging. Despite evidence that age and cognition are linked with similar neural correlates, no previous studies have directly ascertained how these two constructs overlap in the brain in terms of neuroimaging-based prediction. Based on a long lifespan healthy cohort (CamCAN, aged 19-89 years, n = 567), it is shown that both cognitive function (domains spanning executive function, emotion processing, motor function, and memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 88 publications
(135 reference statements)
2
14
0
Order By: Relevance
“…Based on the commonality analyses, the multiple regression models that explained higher variation were driven predominantly by the common effects that Brain Cognition had with the other two, in the case of (Corrected) Brain Age, or with chronological age, in the case of (Corrected) Brain Age Gap. This overlapped variation was consistent with a recent study (Jiang et al, 2022). Altogether, while both the effects of Brain Age and Brain Cognition overlapped with chronological age, Brain Cognition offered additional unique effects that helped improve the ability to capture cognition fluid .…”
Section: Discussionsupporting
confidence: 93%
“…Based on the commonality analyses, the multiple regression models that explained higher variation were driven predominantly by the common effects that Brain Cognition had with the other two, in the case of (Corrected) Brain Age, or with chronological age, in the case of (Corrected) Brain Age Gap. This overlapped variation was consistent with a recent study (Jiang et al, 2022). Altogether, while both the effects of Brain Age and Brain Cognition overlapped with chronological age, Brain Cognition offered additional unique effects that helped improve the ability to capture cognition fluid .…”
Section: Discussionsupporting
confidence: 93%
“…Unlike atlas-based analysis, this framework allows single-scan variability in network representations, which can therefore retain more scan-specific information in the connectivity features (Du et al, 2020). Secondly, we capitalized on advances in machine learning technology to characterize the connectivity signatures of antidepressant outcomes and cognitive changes in a purely data-driven manner (Jiang et al, 2022). Instead of focusing on isolated FNC pairs, the PLS prediction Frontiers in Pharmacology frontiersin.org model concentrates on aggregating thousands of antidepressant outcome-and cognitive change-related FNC changes into a single measure that best captures their neural representations.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 7C, blocks on the main diagonal of the FC matrices represent connections within-module, while blocks off the main diagonal represent connections between-module. Recently, Jiang et al found that, in an older population, connections between the DMN, SMT, and SUB networks were highly predictive for age [43]. They also found that a DMN-SUB connection was correlated with high cognitive performance.…”
Section: A Significant Functional Networkmentioning
confidence: 99%